IMPLEMENTATION AND PROSPECTS OF THE PIPE TOOL IN UZBEKISTAN - Umidjon Urishev (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the popularization of the trumpet, which is one of the leading musical instruments, in the musical culture of Uzbekistan, the conditions and prospects for the formation of the education of musical instruments in Uzbekistan.